KOMUNIKASI ANTARBUDAYA DALAM TRADISI TARUNG PERESEHAN PADA MASYARAKAT BAYAN, KABUPATEN LOMBOK UTARA - Sumada, I Ketut (Widya Sandhi, 2018)
This study aims to study the intercultural communication contained in the tradition of tarung perday in Bayan society, North Lombok regency. This research is designed in the form of descriptive qualitative research in order to provide an understanding of the form, function, and meaning in tarung perday activities involving the participation of the community from various cultural backgrounds. Intercultural communication is done in the form of verbal and nonverbal from the beginning of planning activities until the end of the activity. Intercultural communication serves as a medium for social relations relationships through traditional channels of activity. The implicit meaning behind tarung peresehan is the occurrence of inter-ethnic social bonds that can create a harmonious life together.